The influence of fiscal decentralization, accountability, and financial performance on the level of corruption in Indonesian provincial governments - Dwi Urip Wardoyo; Adinda Hasna Jatmiko (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Corruption is one of the main challenges hindering development and welfare in Indonesia, particularly at the regional government level. This study aims to analyze the effectiveness of anti-corruption programs in provincial governments in Indonesia, focusing on the influence of fiscal decentralization, accountability, and regional financial performance on the level of corruption. The study employs a quantitative approach using panel data obtained from regional financial reports and audit results from the Audit Board of Indonesia (BPK) on provincial governments in Indonesia during the period 2018-2022. The results indicate that fiscal decentralization has a significant impact on the level of corruption, while the variables of accountability and regional financial performance, as measured through audit opinions and regional investment, do not show a significant impact on corruption levels. These findings suggest that although there are financial oversight mechanisms in place, other factors such as transparency, stricter supervision, and public participation in budget management need to be strengthened to enhance the effectiveness of anti-corruption programs at the provincial level. The study recommends the need for a more comprehensive approach to tackling corruption, including governance reforms and strengthening internal controls in each region.